UNIFICATION OF POLITICAL, ECONOMIC AND SECURITY SYSTEMS, CHALLENGE FOR PEACE AND SECURE ON CONDITIONS OF GLOBALIZATION (Annual of the Faculty of Philosophy in Skopje, 2008)
Today, we advert to globalization very often, like a modern and general process, that refers on every field in life. Namely, the globalization is equally political, economic, technological and cultural phenomenon. The globalization is a process for spreading and deepening society relations and institutions in spacious and time dimension. It is a process, which connects the world on all basics; creates bigger interdependence and comprises processes on progressively unifications of all systems at the states. Actually, the process of globalization is composed by many political, economics, cultural, securities and socials phenomenon. These phenomenons 's increasing the interaction between the states and the society, from day to day, making the world civilization much global, much connected, unformatted, transparent and much available for more citizens.This work, which we represent in public, is a result of last analysis of political, economical and securities systems in the states that had began because of globalization process, and they also refers to Republic of Macedonia.
Keywords: GLOBALIZATION; UNIFICATION; POLITICAL SYSTEM; ECONOMIC SYSTEM; SECURITY SYSTEM